Impact of diabetes mellitus on the early phase arterial healing after drug-eluting stent implantation: a multicenter coronary angioscopic study. (25th November 2020) - Ishihara, T; Sotomi, Y; Tsujimura, T; Okuno, S; Iida, O; Kobayashi, T; Hamanaka, Y; Omatsu, T; Higuchi, Y; Mano, T
Abstract: Background: Diabetes mellitus (DM) is a strong risk factor for major cardiac and cerebrovascular events. In particular, coronary artery disease with DM is often complicated with complex lesions. Drug-eluting stents (DES) are mainly used for these lesions, and dual-antiplatelet therapy (DAPT) has been used to prevent stent thrombosis. Early arterial healing after DES implantation may enable short DAPT strategy. However, the impact of DM on the arterial healing in the early phase has not been elucidated to date. Purpose: We evaluated the arterial healing in the early phase after DES implantation using coronary angioscopy (CAS) and compared the findings between DM and non-DM patients. Methods: This study was a multicenter retrospective observational study. We analyzed CAS findings of 337 lesions from 270 patients which were evaluated 3 to 5 months after DES implantation. Patients were divided into two groups: DM (149 lesions in 118 patients) versus non-DM groups (188 lesions in 152 patients). We assessed neointimal coverage (NIC) grades (maximum, minimum and dominant), thrombus adhesion and maximum yellow color of plaque underneath the stent. NIC was graded as follows: grade 0, stent struts were not covered; grade 1, stent struts were covered by thin layer; grade 2, stent struts were buried under neointima. Yellow color was graded as follows: grade 0, white; grade 1, light yellow; grade 2, yellow; grade 3, intensive yellow. Results: Minimum NIC coverage grade was lower in DM group than in non-DM group (P=0.002, Figure), while maximum and dominant NIC coverage grades were similar between them (P=0.94 and P=0.59, respectively). Thrombus adhesion (44.3% versus 38.8%, P=0.32) and maximum yellow color grade (P=0.78) were also similar between DM and non-DM groups. Even after the adjustment by the confounding factors such as follow-up duration and primary disease of acute coronary syndrome, DM was an independent factor predicting grade 0 of minimum NIC (odds ratio [OR] 1.83 [95% confidence interval 1.11–3.03], P=0.019). Conclusion: DM patients showed less covered struts than non-DM patients 3 to 5 months after DES implantation, suggesting that the recent ultra-short DAPT strategy might not be easily applicable to DM patients. Funding Acknowledgement: Type of funding source: None